Sharing Responsibility through Joint Decision Making and Implications for Intimate-Partner Violence : Evidence from 12 Sub-Saharan African Countries - Donald, Aletheia; Doss, Cheryl; Goldstein, Markus P.; Gupta, Sakshi (World Bank, Washington, DC, 2021)
Intimate partner violence affects 36 percent of women in Sub-Saharan Africa. This paper examines the relationship between decision making within couples and the incidence of intimate partner violence across 12 African countries. Using the wife’s responses to survey questions, the analysis finds that compared with joint decision making, sole decision making by the husband is associated with a 3.3 percentage point higher incidence of physical intimate partner violence in the last year, while sole decision making by the wife is associated with a 10 percentage point higher incidence. Similar patterns hold for emotional and sexual violence. When the husband’s report of decision making is included in the analysis, joint decision making emerges as protective only when spouses agree that decisions are made jointly. Notably, agreement on joint decision making is associated with lower intimate partner violence than agreement on decision making by the husband. Constructs undergirding common intimate partner violence theories, namely attitudes toward violence, similarity of preferences, marital capital, and bargaining, do not explain the relationship. The results are instead consistent with joint decision making as a mechanism that allows spouses to share responsibility and mitigate conflict if the decision is later regretted.